Risk of COVID-19 Transmission Aboard Aircraft: An Epidemiological Analysis Based on the National Health Information Platform. (May 2022) - Guo, Qiangqiang; Wang, Jianjian; Estill, Janne; Lan, Hui; Zhang, Juanjuan; Wu, Shouyuan; Yao, Jingwen; Yan, Xuanchen; Chen, Yaolong
Highlights: COVID-19 may be transmitted during a passenger flight. Most confirmed cases were seated in the middle rows of economy class. The prevalence of COVID-19 did not differ among passengers in different seats. Passengers seated in the 2 rows in front of a confirmed case were at a higher risk of being infected. Abstract: Objectives: This study aims to investigate the risk of COVID-19 transmission on aircraft. Methods: We obtained data on all international flights to Lanzhou, China, from June 1, 2020, to August 1, 2020, through the Gansu Province National Health Information Platform and the official website of the Gansu Provincial Center for Disease Control and Prevention. We then performed the statistical analysis. Results: Three international flights arrived in Lanzhou. The flights had a total of 700 passengers, of whom 405 (57.9%) were male, and 80 (11.4%) were children under the age of 14 years. Twenty-seven (3.9%) passengers were confirmed to have COVID-19. Confirmed patients were primarily male (17, 65.4%) with a median age of 27.0 years. Most confirmed cases were seated in the middle rows of economy class or near public facility areas such as restrooms and galleys. The prevalence of COVID-19 did not differ between passengers sitting in the window, aisle, or middle seats. However, compared with passengers sitting in the same row up to 2 rows behind a confirmed case, passengers seated in the 2 rows in front of a confirmed case were at a slightly higher risk of being infected. Conclusions: COVID-19 may be transmitted during a passenger flight, although there is still no direct evidence. Graphical abstract: Image, graphical abstract